Congenital heart disease in low‐and‐middle‐income countries: Focus on sub‐Saharan Africa. Issue 1 (6th February 2020) - Zimmerman, Meghan; Sable, Craig
Abstract: The etiology of congenital heart disease (CHD) is multifactorial. The birth prevalence of CHD is shaped by a wide variety of maternal, fetal, and neonatal risk factors, along with the rates of prenatal diagnosis and terminations of pregnancy, all of which have geographic variability Epidemiology data availability from low‐and‐middle‐income countries (LMIC) on CHD prevalence, morbidity, and mortality are far more limited than from high income countries. Data on specific genetic, environmental, and prenatal risk associated with CHD are almost nonexistent. In this article, we will focus on defining what data are available, genetic risk factors, birth and overall prevalence, morbidity, and the impact of limited access to interventions, both surgery and cardiac catheterizations. We will highlight CHD in sub‐Saharan Africa to detail epidemiology studies in the poorest regions of the world. Existing literature as well as estimates from the Global Burden of Disease Study (http://ghdx.healthdata.org ) form the basis for this review. The intersection of poverty, high fertility rates, and limited access to care results in a unique profile of CHD in LMIC. CHD is not a preventable disease (by most standards), so early detection and access are our key interventions to improve the dire outcomes for children in low‐resources settings of the world.